PLASTIC MATERIAL RECYCLING METHOD AND RECYCLING DEVICE - OYAMA TOSHIHIRO; NISHIDA HARUO; TSUKUKI TAKAYUKI; YAMAMOTO TADASHI (2015)
PROBLEM TO BE SOLVED: To provide a recycling device which can recycle plastic material simply and safely and in a manner to enable scaling-up.SOLUTION: A recycling device 1 comprises a treatment tank 3 that stores plastic material, and a superheated steam generation part 2 which supplies superheated steam at 400°C or less under normal pressure to the treatment tank 3. 【課題】より簡易で安全に、かつスケールアップも可能にプラスチック材料をリサイクルすることのできるリサイクル装置を提供する。【解決手段】リサイクル装置１は、プラスチック材料を収容する処理槽３と、常圧で４００℃以下の過熱水蒸気を処理槽３に供給する過熱水蒸気生成部２と、を備える。【選択図】図１